Oral Aversion in Infants With Congenital Heart Disease: A Single-Center Retrospective Cohort Study*. Issue 3 (March 2022) - Goldstein, Stephanie A.; Watkins, Kimberly J.; Lowery, Ray E.; Yu, Sunkyung; Knight, Rachel M.; Drayton, Amy K.; Sayers, Laura; Gaies, Michael
Abstract : OBJECTIVES: Neonates undergoing cardiac surgery are at risk for oral aversion (OA). OA is not well described outside of the index hospitalization and impacts patients and families. We evaluated the prevalence of OA at 1 year old after neonatal cardiopulmonary bypass (CPB) surgery. DESIGN: Retrospective cohort study. SETTING: Single quaternary care hospital. SUBJECTS: Our cohort included 157 neonates who underwent CPB surgery from 2014 to 2017 and had follow-up data available at 1 year old. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Three feeding experts reviewed the medical record to define children with OA; 30% of charts were evaluated in triplicate for validation. Neonates with and without OA were compared in univariate analysis, and risk factors for OA were explored in a limited multivariable analysis. OA was present at 1 year in 37 patients (23.6%) and other feeding difficulties were present in an additional 29 patients (18.5%). Thirty-eight patients (24.2%) had a feeding tube, including 12 (7.6%) with a gastrostomy tube. Factors associated with OA at 1 year included total ICU days, duration of mechanical ventilation, total number of nil per os days, and number of postoperative days (PODs) until oral feeding initiation (all p < 0.0001). Number of POD until oral feeding initiation remained independently associated with OA at 1 year in multivariable analysis (adjusted odds ratio, 1.08; 95% CI, 1.04–1.12; p < 0.0001). Infants with any oral intake at discharge had lower odds of OA at 1 year (0.21; 95% CI, 0.08–0.5; p = 0.0003). At hospital discharge, 132 patients (84.1%) were taking some oral feeds, and 128 patients (81.5%) received tube feeding. CONCLUSIONS: OA and other feeding difficulties are common at 1 year old in neonates undergoing CPB surgery. Delayed exposure to oral intake may be a modifiable risk factor for OA and efforts to improve early oral feeding could lead to better functional outcomes.